Please wait...
1800-212-7858 (Toll Free)
9:00am - 8:00pm IST all days
8104911739
For Business Enquiry

or

Thanks, You will receive a call shortly.
Customer Support

You are very important to us

For any content/service related issues please contact on this toll free number

022-62211530

Mon to Sat - 11 AM to 8 PM

explain newton's equations of motion in graph method and nermarically

Asked by bhallan.kuldeep 25th July 2019, 8:28 PM
Answered by Expert
Answer:
 
Fig.1 shows the velocity-time graph of uniformly accelerated motion.
Acceleration is defined as rate of change of velocity. Hence for instantaneous acceleration for a given point of motion,
we need to find slope of the velocity-time graph at the required point. For uniformly accelerated motion, acceleration is
constant, hence slope is constant. As per the plotted graph in fig.1, Let us consider a body which is moving with
velocity v1 at an instant of time t1 .

Let v2 be the velocity at time t2 . As shown in figure,  slope = acceleration a = ( v2 - v1 )/( t2 - t1 ) ................(1)
 
Let us put, initial velocity v1 = u and final velocity v2= v and time duration (t2 - t1) = t,
 
Then from eqn.(1),  a = (v-u)/t   or we get   v = u+a t  ............................(2)
 
We know that area under the velocity-time graph is the distance travelled. 
In fig.2, which is a velocity-time graph of uniformly accelerated motion, point-A represents the state of motion at time t1
when the velocity is v1 . Similarly point-B represents the state of motion at time t2 when the velocity is v2 .
 
Area of trapezium ABCD equals the distance travelled between time t1 and time t2 .
 
Area of trapezeium = (1/2)[ AC+BD ]×CD = (1/2)[v1 + v2 ]×(t2 - t1 ) ....................(3)
In eqn.(3), if we put, initial velocity v1 = u , final velocity = v and time duration (t2 - t1 ) = t
 
then we get ,  Area of trapezium = distance S = (1/2)( v + u )×t .....................(4)
 
if we substitute for final velocity v from eqn.(2), then we have, S = (1/2) (u+at+u)×t = u t + (1/2) a t2 ................(5)
 
In eqn.(4), if we substitute for t from eqn.(2), we get,  S = (1/2)(v+u) [ (v-u)/a ]  = (1/2) [ v2 - u2 ] / a  
 
Hence, v2 = u2 + 2 a S  ......................... (6)
Answered by Expert 26th July 2019, 1:51 PM
Rate this answer
  • 1
  • 2
  • 3
  • 4
  • 5
  • 6
  • 7
  • 8
  • 9
  • 10

You have rated this answer /10

Your answer has been posted successfully!

Chat with us on WhatsApp